Children’s Opinion of Retrospective Pre-Post ‘Then-Test’ Survey Validity - Leanne M. Kelly (Journal of MultiDisciplinary Evaluation)
Background: Over the past forty years there have been a number of studies conducted to compare traditional pre-post surveys (pretest-posttests; administered in two stages before and after an intervention) with retrospective pre-posts (thentests or pre-then-post-tests; administered after intervention only, with participants asked to reflect back to complete the ‘pre’ retrospectively). These previous studies have been with adult respondents and overwhelmingly quantitative.